KONTRIBUSI TAMAN HIBURAN RAKYAT SRIWEDARI TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KOTA SURAKARTA PADA TAHUN 2012 – 2016 - Petrania Putri, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2019)
The aims of this research are to analyze the level of contributing accomplishment from Folk Amusement Park (THR) Sriwedari to Original Local Government Revenue (PAD) Surakarta city and to analyze the level of growth rate achievement on Folk Amusement Park (THR) Sriwedari in 2012 – 2016. This research uses a descriptive quantitative research. The research sources are the secondary and primary data. The techniques of collecting data are documentation, interview, and library research. The result shows that the contribution of THR Sriwedari towards Original Local Government Revenue (PAD) Surakarta city is classified in the lowest criteria. The growth rate of THR Sriwedari is classified in the successful criteria, while the growth rate of Regional Tax and PAD Surakarta city is classified in the unsuccessful criteria. Keywords: Contribution, Folk Amusement Park (THR), Original Local Government Revenue